Using Behavioral Biometrics in the Context of Cybersecurity of Polish Banking Sector (2019-2024) - Macierzyński, Wiesław; Macierzyński, Michał (Journal of Finance and Financial Law, 2025)
The purpose of the article. The purpose of the article is verification of the hypothesis that behavioral biometrics may become a solution which will reduce the extent of financial fraud in Poland. The problem in question is notable due to the negative impact of changes on cybersecurity in the environment of banking sector, after the COVID-19 pandemic. Only over the years 2019–2024 there was a tenfold increase in the value of fraud. The risk of financial crime in cyberspace is becoming the major challenge faced by the financial sector. Such high dynamism, as well as the extent of the loss experienced by customers, made supervisory authorities interested in the problem, which resulted in issuing to banks a number of directives concerning educating customers and minimizing the risk of fraud at a system level. One of the directives recommended in this matter to payment service providers is using systems based on behavioural biometrics. This modern technological solution allows to verify in real time whether the person logging in to a bank account and performing financial operations is actually the owner of the account. This paper contains strategic diagnosis of this technology by means of a SWOT analysis. This method allowed to identify and assess key internal factors (strengths and weaknesses) and external ones (opportunities and threats), as well as determining the dominant strategy of development on the financial market in Poland. As a result, the authors formed strategic recommendations both for financial institutions and regulators, which may enhance the effectiveness of behavioural biometrics in reducing financial fraud. Methodology. In the article the qualitative research approach was implemented. The main method of the analysis is the case study of Polish banking sector over the years 2019–2024. Descriptive analysis was used to present the evolution of cyber threats, the extent of financial frauds, as well as regulatory frameworks. The key tool in the research is the SWOT analysis, which allowed to identify strengths and weaknesses of behavioural biometrics, as well as market opportunities and threats. It led to formulating recommendations. Complementarily, secondary data analysis was used. The data derived from reports, publications and statements by the market regulators. The results of the research. From the perspective of financial institutions, behavioural verification may constitute the key factor in eliminating the most common financial frauds. The most effective approach adopted by banks should be proactive use of internal assets of behavioural biometrics to maximize the benefits from external market opportunities. The biggest challenge and the blocker of the development of this technology is a low level of customer acceptance, and the external threat in the form of restrictive legal and regulatory barriers. In this case, a solution should be changing the present process of obtaining a customer’s consent. Connecting the consent with the benefits of convenient using e-banking may considerably increase the index of acceptance, and as a result, eliminate the biggest barrier in the development. It will enable to use the full potential of the solution supported by the development of the sector platform. Although behavioural biometrics plays a lesser role in preventing non-authorised transactions by customers manipulated by criminals, it is an important part of a proactive cybersecurity strategy, especially in the context of the principle of the refund D+1. It is essential in the context of the pressure by regulators which increases the responsibility of banks for fraud transactions. Practical implications. Behavioural biometrics may become a key tool limiting the extent of financial frauds. If implemented, it increases the level of customer protection, and as a result, allows to reduce the extent of financial frauds, especially those related to taking over a bank account. The biggest benefit connected with this technology is constant, non-invasive verification of a customer’s identity in the background. It is an excellent supplement to presently existing anti-fraud systems and solutions. Using sector platform may contribute to a better and faster acceptance, and increasing the efficiency of the security measures used. It will allow banks for a better reaction to incidents, and meeting the regulators’ increasing demands concerning protecting customers. However, the success of implementing and using behavioural biometrics depends on solving the problem of legal barriers, market and customers education, without which the technology will remain only a niche solution.